Hill Runner's Physiology, Performance and Nutrition: A Descriptive Study - Lember, Liivia-Mari; Di Virgilio, Thomas George; Brown, Eilidh MacKenzie; Rodriguez-Sanchez, Nidia (Frontiers in Sports and Active Living, 2021)
Objectives: The aim of this descriptive study was to characterise anthropometric variables, aerobic capacity, running performance and energy intake and expenditure of hill runners in free-living conditions, and to investigate the relationship between age, anthropometric variables, aerobic capacity and running performance. Methods: Twenty-eight hill runners participated in this study (17 males and 11 females; aged 18–65 years). Body fat percentage estimate, sum of eight skinfolds (triceps, subscapular, biceps, iliac crest, supraspinale, abdominal, front thigh and medial calf) and maximal oxygen capacity (VO2max) were assessed in a laboratory setting. Participants also completed a timed hill run (Dumyat Hill, Scotland, ascent: 420 m, distance: 8 km) while wearing a portable gas analyzer to assess oxygen consumption (VO2). Energy intake and energy expenditure were assessed in free-living conditions over three consecutive days different from the testing days through self-reported food diaries and accelerometers. Results: VO2max assessed in the lab (51.2 ± 7.6 ml·min−1·kg−1) showed a weak negative relationship with age [rs(23) = −0.38, p = 0.08]. Neither body fat percentage (median 12.4; IQR 10.1–17.1) nor the sum of skinfolds (median 81.8; IQR 62.4–97.8 mm) correlated with age [rs(28) = 0.001, p = 0.10 and 26 rs(28) = −0.02, p = 0.94, respectively]. The observed intensity of the hill run was 89 ± 6% of the age predicted maximum heart rate and 87 ± 9% of the VO2max observed in the lab. Hill running performance correlated with VO2max [r(21) = 0.76, p < 0.001], age [rs(26) = −0.44, p = 0.02] and with estimated body fat percentage and sum of skinfolds [rs(26) = −0.66, p < 0.001 and rs(26) = −0.49, p = 0.01, respectively]. Energy intake negatively correlated with age [rs(26) = −0.43, p = 0.03], with the overall energy intake being significantly lower than the total energy expenditure (2273 ± 550 vs. 2879 ± 510 kcal·day−1; p < 0.001; d = 1.05). Conclusion: This study demonstrated that hill running performance is positively associated with greater aerobic capacity and negatively associated with increases in adiposity and age. Further, the study highlights that hill runners are at risk of negative energy balance.